Radiation-Induced Polymerization of Acrylamide and Methacrylamide-Based Polymer Gel Dosimeters - Doyan, Aris (2005)
Radiation-induced polymerization of acrylamide and methacrylamide-based polymer gel dosimeters potentially used for the verification of complex dose distributions in 3D associated with conformal radiotherapy has been studied using nuclear magnetic resonance (NMR), Raman spectroscopy and impedance analyzer methods at room temperature. Three polymer gels of polyacrylamide (PAAmG), polymethacrylamide (PMAAmG) and poly(acrylamide-co-methacrylamide) (PAAm-co-MAAmG) were synthesized in oxygen free condition from acrylamide (AAm) and methacrylamide (MAAm) as monomers and N, N'-methylene-bis-acrylamide (BIS) as Crosslinker at various concentration from 2% to 6% and 6% gelatin. The comonomers (AAm, MAAm and BIS) were dissolved in an aqueous gelatin